German companies engaging in China: Decision-making processes at home and management practices in Chinese subsidiaries - Geny Piotti (Max Planck Institute for the Study of Societies, 2009)
This paper attempts to explain why internationalization processes to China are growing despite the significant difficulties that foreign direct investments into China encounter. The answer to this question can be found in the processes of decision-making on internationalization at the company level and how these affect management practices in Chinese subsidiaries. The argument I put forward in this paper is that for the small and medium-sized enterprises the study focuses on, the decisions concerning investment in China are mainly the product of structural and legitimation pressure. Structural pressure can encourage cognitive mechanisms and behavioral consequences similar to those occurring when individuals (and organizations) cope with threat. Legitimation pressure can foster wishful thinking, which pushes actors to believe that desired options are good despite evidence to the contrary. These pressures have an impact on how well companies are prepared when they internationalize and can particularly affect some crucial management practices, leading to inefficiencies and problems in subsidiaries. – – Warum steigt die Anzahl der Unternehmensverlagerungen nach China, obwohl westliche Unternehmen dort auf große Schwierigkeiten treffen? Aufschluss darüber können unternehmerische Entscheidungsprozesse geben, die der Unternehmensverlagerung zugrunde liegen, und deren Auswirkungen auf Geschäftsführungspraktiken in den chinesischen Niederlassungen. Ich argumentiere, dass mittelständische Unternehmen, auf die sich das Interesse dieser Studie richtet, sich vor allem wegen struktureller Zwänge und eines hohen Legitimierungsdrucks zu einer Investition in China entscheiden. Strukturelle Zwänge können kognitive Mechanismen auslösen und Verhaltensweisen hervorrufen, die mit Reaktionen von Individuen (und Organisationen) auf eine Bedrohung vergleichbar sind. Legitimierungsdruck kann Wunschdenken fördern und Akteure dazu bringen zu glauben, die gewünschten Optionen seien gut, obwohl Beweise für das Gegenteil vorliegen. Diese Zwänge haben somit einen Einfluss darauf, wie gut Unternehmen auf eine Internationalisierung vorbereitet sind, und können wichtige unternehmerische Maßnahmen entscheidend beeinträchtigen. Dies führt in der Folge zu Ineffizienz und Problemen in den Niederlassungen.
Keywords: 300; Multinationales Unternehmen; Deutsch; Auslandsproduktion; Unternehmenspolitik; Auslandsniederlassung; China